Accountability Of Directors In Dividend Distribution As A Form Of Legal Protection For Shareholders - Siti Junaidah Hasibuan (SEAN Institute, 2024)
The Principle of Accountability is a way to account for success or failure in implementing the company's vision and mission, to achieve the goals and objectives that have been set. In other words, accountability is the periodic responsibility of the company's management.Directors have an obligation to act in good faith, carry out the functions of managing the company, and protect the interests of the company and its shareholders, in this case, limiting the distribution of dividends. They must make rational decisions, based on careful consideration and adequate information. However, there are several issues that need to be considered regarding the responsibilities of directors in the company. One potential problem is the occurrence of legal violations by directors, whether intentional or unintentional. In this case, there needs to be an effective monitoring and accountability mechanism to ensure that directors are responsible for their actions. This research aims to analyze the responsibilities of directors in distributing dividends in an effort to legally protect shareholders. This study uses literature analysis methods to collect data from various legal sources, such as laws, as well as related literature.